Sodium iodide dopant mediated enhancements in energy storage characteristics of polysaccharide polymer electrolytes - Shetty, Supriya K.; Ismayil; Nayak, Pradeep; Sudhakar, Y.N.; Noor, I.M. (Elsevier, 2024)
Sodium iodide dopant influencing the properties of polysaccharide polymer sodium carboxymethyl cellulose is analyzed in this work by FTIR, XRD, DSC, TGA, SEM, UTM, and electrical. Solvation of I− and Na+ ions by the −OH group has disrupted the intra– and intermolecular hydrogen bonds between the polymers escorting to a decrease in crystallinity and creating a pathway for ion diffusion. The formation of transient crosslink and the physical environment created by the polymer-ion interaction have affected the rigidity of the polymer chains as well as the thermal stability of the NaCMC−NaI system. I− ion influences the ESW of the NaCMC−NaI system by forming various iodine species. Trapping of the I− ion for the NaCMC70−NaI30 sample has resulted in a drop in ionic conductivity manifested in the transient ionic current curve. A cation transference number of 0.14 indicates the dominance of anion in the ion conduction mechanism. An energy density of 720 mWhkg−1 and power density of 60 mWkg−1 was achieved for a dry cell incorporated with a CI25 sample as the electrolyte and separator.